EVALUASI LAJU PERTUMBUHAN DAN SINTASAN IKAN NILA (Oreocromis niloticus) YANG DIBUDIDAYA DALAM EMBER (BUDIKDAMBER) - Fadly, Fadly; Henggu, Krisman Umbu (Marinade, 2021)
Tilapia is a type of consumption fish that is very popular with the community, has an affordable price and is easy to cultivate. However, limited land for cultivation is one of the obstacles for the community in cultivating tilapia (Oreochromis niloticus). One alternative solution that needs to be done is the Budikdamber activity. Budikdamber is a method of cultivating fish in a limited space with high effectiveness if done intensively. The aim of this study was to evaluate the growth rate of tilapia (Oreochromis niloticus) and survival during the cultivation of damber activities. The results showed that tilapia fry (Oreochromis niloticus) cultured in buckets (budikdamber) for 6 weeks of rearing had a significant average increase in length and weight after the adaptive phase in the first and second weeks. The average increase in length and weight of tilapia during cultivation reached 1 cm/week, increased body weight of 20 grams/head and had a 100% survival rate.